2003
DOI: 10.1046/j.1471-4159.2003.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine‐induced serotonergic neurotoxicity in mice: lack of neuroprotection by inhibition/ablation of nNOS

Abstract: Previous studies have implicated a role for nitric oxide (NO) and peroxynitrite in methamphetamine-induced dopaminergic neurotoxicity. The present study was undertaken to investigate whether NO is involved in serotonergic neurotoxicity caused by fenfluramine. In the first experiment, the effect of the neuronal nitric oxide synthase (nNOS) inhibitor 7-nitroindazole (7-NI; 25 mg/ kg · 4) on fenfluramine (25 mg/kg · 4)-induced serotonergic neurotoxicity in Swiss Webster mice was investigated. In the second experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The amphetamine doses chosen were based on our previous studies on the neurotoxic effects of METH (Itzhak and Ali, 1996;Itzhak et al, 2002); FEN (Itzhak et al, 2003b), and MDMA (Itzhak et al, 2003a) in Swiss Webster mice. Control mice received saline (0.9% NaCl) injections.…”
Section: Schedule Of Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphetamine doses chosen were based on our previous studies on the neurotoxic effects of METH (Itzhak and Ali, 1996;Itzhak et al, 2002); FEN (Itzhak et al, 2003b), and MDMA (Itzhak et al, 2003a) in Swiss Webster mice. Control mice received saline (0.9% NaCl) injections.…”
Section: Schedule Of Drug Administrationmentioning
confidence: 99%
“…We have previously shown that METH and FEN selectively deplete dopaminergic (Itzhak and Ali, 1996) and serotonergic (Itzhak et al, 2003b) markers, respectively, while MDMA reduces both DA and 5-HT markers in Swiss Webster mice (Itzhak et al, 2003a;Itzhak and AchatMendes, 2004). Using these mouse models, we investigated the effect of amphetamines-induced injury to individual monoamine systems on CPP and CPA.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, administration of METH (5 mg kg 71 63; 3 h apart) to Swiss Webster mice caused selective depletion of striatal DA, DA metabolites 3,4-dihydroxyphenylacetic acid (DO-PAC), homovanillic acid (HVA) and DAT binding sites, with no evidence of 5-HT depletion (26). Administration of fenfluramine (25 mg kg 71 62; 6 h apart; for 2 days) caused selective depletion of 5-HT and 5-HT transporter (5-HTT) binding sites in striatum, frontal cortex and hippocampus with no evidence of dopaminergic neurotoxicity (27). However, administration of MDMA (15 mg kg 71 62; 8 h apart, for 2 days) caused marked depletion of striatal DA and DAT binding sites as well as depletion of 5-HT in the striatum and hippocampus, and depletion of 5-HTT binding sites in the frontal cortex.…”
Section: Animal Studiesmentioning
confidence: 99%
“…To test this hypothesis we investigated whether blockade of nNOS or ablation of nNOS (KO mice) provides protection against serotonergic neurotoxicity induced by the amphetamine analog fenfluramine (27). We found that neither inhibition of nNOS by 7-NI in Swiss Webster mice nor the absence of the nNOS gene in the nNOS (7/7) mice afforded protection against serotonergic neurotoxicity caused by high doses of fenfluramine (25 mg kg 71 62; for 2 days).…”
Section: Mechanisms Of Neurotoxicitymentioning
confidence: 99%
“…MDMA (single or repeated doses) had no effect on striatal 5-HT or 5-HIAA levels. The same group of authors (Itzhak et al, 2003) has reported that nNOS inactivation (by gene knockout) or submaximal inhibition of nNOS activity by a high dose of 7-nitroindazole (25 mg/kg i.p.) failed to protect central serotonergic systems in Swiss Webster mice against the long-term 5-HT depleting effect of a high-dose treatment regimen with d,l-Fen (25 mg/kg i.p., twice daily for two days) suggesting that NO-dependent mechanisms have no major role in the serotonergic actions of Fen.…”
Section: Role Of Nos No and Peroxynitrite In The Neurotoxicity Of MDmentioning
confidence: 95%